K-SHELL IONIZATION AND X-RAY PRODUCTION CROSS SECTIONS BY PROTONS IN VACUUM AND GASEOUS ENVIRONMENT - Kallithrakas-Kontos, N.; Katsanos, A. A. (HNPS Advances in Nuclear Physics, 2020)
The Κα ionization and x-ray production cross sections from the bombardment of three metal targets with protons were measured in vacuum and in gaseous environment (external beam technique). Proton energies between 1.5 and 8 MeV were used. The experimental Κ shell ionization and x-ray production cross sections were calculated for the same targets and com pared with three theoretical and two semiempirical approxima tions. For the measurements in gaseous environment the influence of the secondary electrons (delta electrons) emitted from the gas, to the x-ray yields was investigated. For this pur pose a suitable model was introduced and tested experimentally.